The use of 3,4-Methylenedioxymethamphetamine (MDMA) in the treatment of Post-Traumatic Stress Disorder (PTSD) - review - Womperski, Karol; Bogacz, Rafał; Gaik, Magdalena; Magda, Inga; Woźniak, Justyna; Uram, Ewa; Osuch, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Post-traumatic stress disorder (PTSD) is a common health issue of complex etiology significantly deteriorating functioning in everyday life. It may develop as a result of exposure to traumatic events like traffic accidents, war experience, sexual abuse and domestic violence. Current methods of treatment consist of trauma-oriented psychotherapy supported by selective serotonin reuptake inhibitors (SSRIs). Their efficacy is far from satisfactory thus a search for alternative methods is necessary. 3,4-Methylenedioxymethamphetamine (MDMA) commonly known as “ecstasy” seems to have promising results in the treatment of PTSD. Aim of study: Review of current knowledge about MDMA-assisted therapy in PTSD, its possible mechanisms of action, efficacy and safety. Methods and materials: A review of chosen literature from in PubMed database, GoogleScholar database in the years 2000-2023 was conducted using the following keywords: “PTSD epidemiology”, “PTSD pathophysiology”, “PTSD neural activity”, “PTSD brain activity”, “MDMA PTSD”, “MDMA brain activity”, “MDMA neural activity”, “MDMA neurotoxicity”, “MDMA PTSD therapy”, “MDMA safety”, “MDMA caffeine” Results: MDMA-assisted therapy has promising effects in PTSD treatment and its safety profile is satisfactory. The improvement in symptoms occurs most likely due to its modulating activity on brain structures responsible for threat detection and emotion processing. Conclusions: Further research is necessary to assess MDMA-assisted therapy in PTSD, especially direct comparison of its efficacy versus first-line treatment SSRIs and assessment of its long-term-safety.